Perceived health, attractiveness and symmetry, with a test of the ability of Homo sapiens to discriminate facial symmetry across species. - Yang, Shanshan. (2009)
Proportion and symmetry are thought to be very important for animals to appreciation their daily life. This study aims to explore if facial asymmetry affects interspecific perception of health, beauty, and symmetry. Previous study show there is positive relationship between symmetry and perceived health and attractiveness, while our study proved otherwise. Results supported confirmed the indicative role that facial symmetry played in attractiveness but not in health perception. The possible reasons are discusses and the perception in relation to phylogenic relationship is also tested.